Hearing aids for otitis media with effusion: Do children use them?. (August 2017) - Gan, Richard Wei Chern; Overton, Parisa; Benton, Claire; Daniel, Matija
Abstract: Introduction: ENT surgeons may refer children with otitis media with effusion (OME) to audiology for consideration of hearing aids. They are an option for the treatment of OME, but are only effective if the child actually wears them. Our study investigated what proportion of children referred for hearing aids actually receive them, and whether children use them. Method: Retrospective study of children referred to audiology from November 2013 to August 2014, including 70 children referred by ENT for hearing aids for OME, plus a further 5 children with OME given hearing aids through direct access audiology service. Results: During the study period, there were 202 referrals of children to audiology, of which 70 (34.7%) were for consideration of hearing aids for OME. Of these 70 referred children, 37 (52.9%) were not fitted with hearing aids due to normal audiometry (23), asymptomatic mild hearing loss (7), nonattendance (3), clinical decision to just monitor hearing (1), parental decline (2), and unrecorded reason (1). A total of 38 children (including direct access patients) were fitted with hearing aids for OME. Majority (36/38) of children issued aids used them, 16 all day, 7 only at school, 1 only at home, 3 only when needed, and 9 used them for an unspecified duration; 1 child's use of hearing aids was unrecorded, and 1 child refused to use it. 21 were fitted bilaterally and 17 unilaterally. 37 were behind the ear aids and 1 a BAHA softband. Conclusions: A third of referrals to paediatric audiology by ENT are for consideration of hearing aids for OME. Only about half of children referred to audiology for hearing aids for OME actually receive them, as by the time they see audiology the hearing loss has frequently resolved or is asymptomatic so that aiding is unwarranted. Once fitted, they appear to be well accepted. Hearing aids have fair utilization in children fitted with them for OME.